Effectiveness and safety of deucravacitinib treatment for moderate-to-severe psoriasis in real-world clinical practice in Japan - Teppei Hagino; Hidehisa Saeki; Eita Fujimoto; Naoko Kanda (Journal of Dermatological Treatment)
Background Deucravacitinib is a selective oral tyrosine kinase 2 (TYK2) inhibitor recently approved for psoriasis.Objectives We aimed to evaluate the real-world effectiveness and safety of deucravacitinib for psoriasis.Methods We analyzed 33 Japanese patients with psoriasis (23 with plaque psoriasis, eight with psoriatic arthritis, and two with erythrodermic psoriasis) from January 2023 to October 2023. All patients received deucravacitinib 6 mg daily until week 16.Results At week 8, 12, or 16, the achievement rate of PASI 75 was 60.9%, 73.9%, or 78.3%, that of PASI 90 was 13.0%, 39.1%, or 52.2%, that of PASI 100 was 0%, 8.7%, or 13.0%, that of absolute PASI ≤2 was 34.8%, 65.2%, or 78.3%, respectively. The achievement rate of dermatology life quality index 0/1 at week 16 was 42.9%. Fourteen patients (42%) complained pruritus. Peak pruritus-numerical rating scale in patients with pruritus decreased by median [interquartile] 71.4 [50–80] % of baseline at week 2. Adverse events occurred in 18.2% of patients, which were mild and manageable.Conclusions Deucravacitinib for patients with psoriasis was well-tolerated and gave favorable therapeutic effects in the real-world practice. Deucravacitinib treatment rapidly reduced pruritus.